PopularMMOs Presents: Enter the Mine - Book 2 - Pat + Jen (YouTube personality); Jones, Dani, 1983- (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2019)
"After Pat and Jen saved Bomby, their cat Cloud, and one hundred friendly zombies from the clutches of Evil Jen and brought them home from the underworld, they thought their adventuring days were over. But ever since their return, more mysterious new holes have started appearing--and more and more of their friends have started disappearing! After Jen stumbles into one and Pat rushes after her, they find themselves trapped in a dark, dank boomium mine. Now Pat and Jen need to free their friends, figure out whos behind this evil plot, and find a way to get back home-- before its too late."--Amazon.
Keywords: Video games -- Comic books, strips, etc; Adventure stories -- Comic books, strips, etc; Zombies -- Comic books, strips, etc; Unicorns -- Comic books, strips, etc; Video games -- Fiction; Adventure and adventurers -- Fiction; Missing persons -- Fiction; Unicorns -- Fiction; Good and evil -- Fiction; Action and adventure comics; Comic books, strips, etc; Fantasy comics; Graphic novels; Comic books, strips, etc; Fantasy comics; Action and adventure comics; Comics (Graphic works); Graphic novels